A apropriação do conceito de divisão por alunos dos anos iniciais do ensino fundamental - Silva, Alexsandra Lúcia Miranda Lima Senna da (2014)
This master dissertation with focus in mathematics education took place within the Graduate Education Program at Center of Education at Federal University of Espírito Santo. Our research occurred in 2013 in a public school in the city of Vitória, ES. Our qualitative research investigates are the 3 rd grade Elementary School students strategies and ideas about division. In addition, we conducted a teaching experiment in the classroom working with some activities that explored the concept of division. We answered the following questions: Which strategies and ideas about division the 3rd grade (4th year) Elementary School students show before and after a formal teaching experiment about division? The studies of Gómez Chacón, Lorenzato, Polya, Santos, Santos-Wagner, Selva, Serrazina, e Vigotsky, among others, offered theoretical contributions to this work. We collected data through lessons observed, activities solved by students and classes taught by the beginner researcher teacher. The analysis procedures occurred under the light of the cited authors. Students were encouraged to establish relationships, conjecture and argue about their conclusions throughout the educational tasks. The experience with these activities contributed to a change of students’ attitudes, leading them to become more reflective and active in math classes. Furthermore, we believe that changes with respect to division’s conceptions and division’s teaching strategies occurred with both the classroom teacher and the beginner teacher researcher. We, also, observed the development of students' autonomy in seeking new mathematics learning situations and strategies to solve and elaborate problems. We hope this research will inspire other teachers to develop pedagogical practices that prioritizes the construction of the concepts in match and the usage of their own strategies. We dream that the teachers feel that it is important to consider peculiarities, particularities and abilities of all the ones who are mathematics and learning process.